Comparative study of the effect of oral administration of chloral hydrate and intranasal fentanyl on sedation in children for electroencephalography - Shafa , Amir; Khodarahmi, Amir; Shahhosseini , Sedighe (Iranian Journal of Child Neurology, 2023)
Objectives Sedation and stability during electroencephalography (EEG) in pediatrics have high clinical importance. This study compares the sedative properties of oral chloral hydrate (OCH) and intranasal fentanyl (INF). Materials & Methods This study was a randomized clinical trial conducted in 2020 in Isfahan City on sixty-two pediatric candidates for EEG. Patients were randomized into two groups receiving 50 mg/kg OCH and 2 μg/kg INF thirty minutes before the process. The heart rate (HR), mean arterial pressure (MAP), respiratory rate (RR), and oxygen saturation (O2 sat) of patients, sedation, and physician’s satisfaction were measured and compared between groups. Results The HR of patients decreased significantly in both groups (P< 0.001), and the patients that received INF had significantly lower HR 15, 30,45, and 60 minutes after drug administrations (P< 0.05). RR evaluation indicated significantly decreased RR in both groups (P< 0.001), and patients receiving INF had lower RR 30, 45, and 60 per minutes after drug administrations (P< 0.001). Both groups showed significantly increased sedation levels during the study (P< 0.001), and patients treated with INF had higher sedation levels 15, 30, and 45 minutes after drug administration. Satisfaction rates were higher among the group that received INF (P= 0.020). Conclusion use of intranasal fentanyl had significant analgesic and sedative effects on pediatrics undergoing EEG.